Sistem Pembuatan Jaminan Tender Pada Perusahaan Jasa Pembuatan Asuransi - Dewi, Linda Sari; Arisawati, Ester; Sihombing, Erene Gernaria; Maulida, Linda (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2018)
A loss-making service company does not yet have a website on the information of making a Tender Guarantee as a prospective principal registration medium that will use our services for the manufacture of warranties. From the system that will be made to facilitate the making of guarantee which is certificate of Bank Guarantee. The purpose of this study to produce a system of information creation and website-based registration and registration. Online information is an important part of the development of technology in the internet world. The use of website media is very profitable for many parties, for the principal or the party of the company making the loss insurance services. The design of information systems making of this guarantee is made to assist and simplify the entire process of making the existing collateral in the company.